Exploring Museums as Authentic Learning Resources in Social Studies Education within the Merdeka Curriculum Framework - Syafira rahmadhani; Rizka Fadliah Nur; Rahmadiani Rahmadiani (Department of Social Studies Education, Faculty of Tarbiyah and Teacher Training, Datokarama State Islamic University of Palu, Central Sulawesi, Indonesia., 2026)
The use of museums as Social Studies learning media in junior high schools remains incidental and has not been systematically integrated into the curriculum, so their educational potential has yet to be fully utilized. This study aims to examine the perceptions of teachers and students regarding the use of museums as Social Studies learning media and to identify the forms of their compatibility within the Merdeka Curriculum framework at SMPN 3 Palu. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews with three teachers and eight students, and documentation study. The findings reveal that both teachers and students hold positive perceptions toward museums as authentic learning resources capable of providing real and contextual experiences. Museum utilization was carried out in three forms: structured field visits, museum-based projects within the Pancasila Student Profile Strengthening Project, and indirect use of museum documentation in the classroom. All three forms demonstrated strong alignment with Social Studies learning objectives and the Merdeka Curriculum scope. Nevertheless, museum utilization remains suboptimal due to budget constraints, the absence of visit guides integrated with lesson plans, and the lack of formal cooperation between the school and the museum. This study recommends that teachers develop systematic visit planning, schools establish formal partnerships with museums, and education authorities formulate integrated guidelines for museum use as Social Studies learning resources. This study contributes to the development of contextual learning resources in Social Studies education by demonstrating the alignment between museum-based learning and the implementation of the Merdeka Curriculum.